Rewritable Macromolecular Data Storage with Automated Read‐out. (13th February 2022) - Soete, Matthieu; De Bruycker, Kevin; Du Prez, Filip
Abstract: Rewriting data stored on synthetic macromolecules is an interesting feature, even though it is considered as being quite challenging within the area of digital macromolecules. In this context, we initially studied a strategy for modifying the position tag of sequence‐encoded macromolecules in a reversible manner. The efficiency of this method, which relies on the orthogonal cleavage of a thioester moiety via aminolysis, was demonstrated by modifying parts of an exemplary sentence. Simultaneously, a novel algorithm was developed to ease the read‐out of macromolecular information by means of MS/MS techniques. This program, Oligoreader, can identify potential information‐containing macromolecules from a series of MS 1 spectra, analyze the corresponding MS 2 spectra, and finally decode the data. Consequently, the algorithm simplifies the entire read‐out process by avoiding any interference from the operator, which increases the potential for blind sequencing of uniform macromolecules. Abstract : The rewriting of information stored on synthetic macromolecules is achieved via the introduction of an editable position tag. The automated read‐out is facilitated by making use of an algorithm that is able to decode large portions of macromolecular information without interference from the operator.